If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-5 + -3x) = 116 (-5 * -4 + -3x * -4) = 116 (20 + 12x) = 116 Solving 20 + 12x = 116 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 12x = 116 + -20 Combine like terms: 20 + -20 = 0 0 + 12x = 116 + -20 12x = 116 + -20 Combine like terms: 116 + -20 = 96 12x = 96 Divide each side by '12'. x = 8 Simplifying x = 8
| 25x^2+30=55 | | B-24.6=5.1b | | 2+x/4=-2 | | 2(5.5)+3(5.5+1.5)= | | 2(4-20)=8(x-5) | | 6x+52=2x+24 | | B-24.6=5 | | 4p-15=1 | | x/5-7=x+6/3 | | 3+12=9y+4-8y | | 16=x/11 | | 1/x+3/7=5/x | | 5(x+8)=0 | | 7x+3(2x)=39 | | 4(2x-1)-2(3x+5)=x+4 | | 2/3+x^2-5/6+x=0 | | 12+d+8+4d= | | 2/3x^2-5/6x=0 | | 2/3x^2-5/6x | | 5/11x5/12 | | 2(1+5x)=82 | | 24=4x-10 | | 10(r-6)/10r | | -b+2=-.5 | | 5+9x=1+3x | | 6x+3x+x= | | 12y+6-11y=14.5 | | 8x+2x=40 | | 10=4a+10 | | 5/3x=1/x+2 | | 9h-15=75 | | (4+2x)2=2+-2 |